Quantitative Analysis of Abamectin, Albendazole, Levamisole HCl and Closantel in Q-DRENCH Oral Suspension Using a Stability-Indicating HPLC-DAD Method - Hazim M. Ali; Mohammed Gamal; Mohammed M. Ghoneim; Lobna Mohammed Abd Elhalim (Molecules, 2022)
Combination therapy of many anthelmintic drugs has been used to achieve fast animal curing. Q-DRENCH is an oral suspension, containing four different active drugs against GIT worms in sheep, commonly used in Australia and New Zeeland. The anti-parasitic drugs are Albendazole (ALB), Levamisole HCl (LEV), Abamectin (ABA), and Closantel (CLO). The main purpose of this study is to present a new simultaneous stability-indicting HPLC-DAD method for the analysis of the four drugs. The recommended liquid system was 1 mL of Triethylamine/L water, adjusting the pH to 3.5 by glacial acetic acid: acetonitrile solvent (20:80, v/v). Isocratic elusion achieved the desired results of separation at a 2 mL/min flow rate using Zorbax C-18 as a stationary phase. Detection was performed at 210 nm. The linearity ranges were 15.15 to 93.75 μg/mL for ALB, 25 to 150 μg/mL for LEV, 30 to 150 μg/mL for ABA, and 11.7 to 140.63 μg/mL for CLO. Moreover, the final greenness score was 0.62 using the AGREE tool, which reflects the eco-friendly nature. Moreover, the four drugs were determined successfully in the presence of their stressful degradation products. This work presents the first chromatographic method for simultaneous analysis for Q-DRENCH oral suspension drugs in the presence of their stressful degradation products.